Proline-Glycine Dipeptidic Derivatives of Chiral Phosphoramides as Organocatalysts for the Enantiodivergent Aldol Reaction of Aryl Aldehydes and Isatins with Cyclohexanone in the Presence of Water - Cruz-Hernández, Carlos; Hernández-González, Perla E.; Juaristi, Eusebio (Synthesis, 2018)
The synthesis of several novel organocatalysts derived from (R)- and (S)-proline-glycine dipeptides and incorporating a chiral phosphoramide fragment was accomplished. These chiral compounds catalyze the enantioselective aldol addition reaction of cyclohexanone to prochiral aryl aldehydes and isatins in the presence of water. These chiral organocatalysts represent some of the few proline-derived compounds capable to catalyze aldol-type addition of cyclohexanone to isatins, a C–C bond forming transformation for which chiral primary amines are usually more successful. Additionally, these phosphoramide-containing catalysts afforded excellent results in the addition of cyclohexanone to aryl aldehydes, as anticipated by the presence of the proline moiety. The present report includes a detailed evaluation of the new multifunctional catalysts that are able to afford either enantiomer of the chiral product by adequate selection of the configuration of the proline residue.
Keywords: asymmetric organocatalysis; double hydrogen bond donor; dipeptides; hydrophobic interactions; Brønsted acid; Lewis base